The Ball-room instructer [sic]; containing a complete description of cotillons and other popular dances, with illustrations. (New York, Huestis & Craft, 1841)
This manual, small enough to fit into a pocket, declares that it contains "all the information which is interesting to the world of dancing" [p. 5]. In fact, like many nineteenth-century dance manuals, the text is heavily borrowed from numerous sources and compiled by a publisher. Its format is common for this type of manual. It begins with a discussion on etiquette followed by a description of quadrilles--popular group dances performed by four couples facing in a square. Although the waltz was a staple of the mid-nineteenth-century ballroom, it is not discussed in this manual.
Source: Source unknown.
Available also through the Library of Congress Web site as facsimile page images and full text.
Keywords: Ballroom dancing -- Handbooks, manuals, etc; Dance Instruction and Technical Manuals